Record of proceedings (The Institute [S.l.], 1999)
Includes the proceedings of the four statutory meetings held during 1999. Contains the agreements and recommendations that the different statutory organs of the Pan American Insttitute of Geography and History adopted during 1999.
Keywords: GEOGRAPHY